Interspecies bacterial horizontal gene transfer of NDM-1 plasmid in biofilm and planktonic cultures - Zhang, Junshun (2014)
blaNDM-1 gene encodes for the New Delhi metallo-β-lactamase-1 (NDM-1), a type of extended-spectrum beta-lactamase (ESBL) that is responsible for multi-drug resistance. Since its discovery in 2009, it has been detected in nosocomial pathogens like Klebsiella pneumoniea and Pseudomonas aeruginosa from clinical isolates worldwide. Most bacteria exist as biofilms to enhance survival through interspecies interaction, one of which is horizontal gene transfer (HGT). The objective of this study is to investigate factors that affect interspecies HGT of blaNDM-1 plasmids and observe HGT in biofilm in through epifluorescence microscopy. HGT assays were done using clinical isolates of E. coli, K. pneumoniae and C. amalonaticus as donors while E.coli J53was used as recipient. It was discovered that temperature had a significant impact on HGT efficiency in K. pneumoniae and it was also the least efficient at disseminating blaNDM-1. To visualize HGT in biofilm, the donor P.aeruginosa PAO1 tagged with two fluorescent proteins (GFP and RFP) was cultivated with naturally competent P. stutzeri in static biofilm systems. HGT was not observed between P.aeruginosa and P. stutzeri due to indiscernibly low RFP expression which highlighted several parameters that need to be optimized in visualizing HGT in situ.